PENDEKATAN THREE FACTOR MODEL PADA SEKTOR PROPERTY, REAL ESTATE DAN KONSTRUKSI BANGUNAN - Wijaya, Erric (Economic Faculty, Attahiriyah Islamic University, 2019)
This paper aims to confirm the existence of asset pricing model formulated by Fama and French (1996) by combining size, book to market equity (BE/ME) to risk premium (beta) in Capital Asset Pricing Model (CAPM) that was formulated by Sharpe (1964), Lintner (1965), and Black (1972) then implement it on 45 companies in the real estate, property, and construction building sector in Indonesia Stock Excange in the period 2014-2017. The paper adapts the Fama and French methodology using size and book to market equity (BE/ME) sort then forms portfolios based on historical data of returns, market capitalization, and book value. This study uses time-series data that examines for 48 months. The proposed methodology offers investors the opportunity to construct portfolio management strategies optimally. Moreover, it gives a new insight to portfolio managers in order to increase stock returns by investing in small capitalization firms. The obtained results show that the explanatory power of the Fama-French three-factor model only works significantly on the risk premium (beta) and book to market equity (BE/ME) factors, but does not work on size factor. Key words: Capital Asset Pricing Model, Fama-French Three-Factor Model, Portfolios, Stock Returns